2015
DOI: 10.14583/2318-7670.v03n02a11
|View full text |Cite
|
Sign up to set email alerts
|

Influência do Substrato na Produção de Mudas de Espécies Medicinais

Abstract: Recebido em novembro/2014; Aceito em março/2015. RESUMO:Uma das problemáticas para a produção de mudas de espécies florestais em larga escala é seu crescimento, na maioria das vezes, lento e desuniforme, mesmo utilizando substratos indicados para a área florestal. Dessa forma, objetivou-se analisar, em casa de vegetação, a influência do substrato comercial Basaplant® no crescimento e na nutrição de Copaifera langsdorffii Desf. e de Genipa americana L. O experimento foi disposto em delineamento inteiramente cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…The growth of the root collar (RC) diameter of copaiba seedlings was also greater in the treatment with carnauba residue (2.97 mm), as seen in Table 4. The same value was found by Vieira and Weber (2015) in copaiba seedlings 120 days after transplanting to tubes with 60% Basaplant® and 40% soil. Taking into account the values of the root collar diameter recommended by Xavier et al (2009), above 2 mm for forest species seedlings, all treatments resulted in seedlings that were appropriate to plant in the field.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The growth of the root collar (RC) diameter of copaiba seedlings was also greater in the treatment with carnauba residue (2.97 mm), as seen in Table 4. The same value was found by Vieira and Weber (2015) in copaiba seedlings 120 days after transplanting to tubes with 60% Basaplant® and 40% soil. Taking into account the values of the root collar diameter recommended by Xavier et al (2009), above 2 mm for forest species seedlings, all treatments resulted in seedlings that were appropriate to plant in the field.…”
Section: Resultssupporting
confidence: 84%
“…However, goat manure presented the lowest quantity of phosphorus among the residues evaluated (Table 1). Much lower values were found by Vieira and Weber (2015), where the highest mean of P in copaiba seedlings at 120 days was 0.47 g . kg -1 when testing substrates constituted by different proportions of soil and commercial substrate Basaplant®.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Indirect scaling is cheaper than direct scaling and can be done by using a Wheeler's pentaprism, a Bitterlich relascope, a Barr dendrometer, or a Criterion, for example (Nicoletti et al 2012). Studies assessed indirect scaling using Criterion RD 1000 compared with direct measurements and observed that indirect scaling is reliable and introduces no tendency to the results (Curto et al 2019;Nicoletti et al 2015b;. For example, Nicoletti et al (2015a) compared indirect measurements from the optical dendrometer Criterion 400 and RC3H with direct measurements from destructive scaling and found that indirect scaling was reliable, and that Criterion 400 was the most dependable instrument.…”
Section: Introductionmentioning
confidence: 99%